Agressive behavior, victimization, and problematic use of video games in schoolchildren of primary education from the province of Granada - Chacón-Cuberos, Ramón; Espejo-Garcés, Tamara; Martínez-Martínez, Asunción; Zurita-Ortega, Félix; Castro-Sánchez, Manuel; Ruiz-Rico Ruiz, Gerardo (Revista Complutense de Educación, 2018)
Misuse of digital leisure produce several cognitive and emotional problems in children of school age. In this sense, the use of violent video games can generate disorders on prosocial behavior in younger sectors of population, being linked to aggressive behaviors of different type. This descriptive and cross-sectional study, which was carry out on a sample of 519 student (M = 11.77 ± 1.19) of Primary Education from the province of Granada, aims to determine the relationship between violent behaviour at school, kind of victimization and problematic use of video games and its type. The main instruments employed were the Scale of Aggressive Behaviour at School (Little, Henrich, Jones, & Hawley, 2003), the School Victimization Scale (Mynard & Joseph, 2000), and the Questionnaire of Experiences related to Video games (Chamarro et al., 2014). Results show that children, who suffer potential and severe problems related to video games, had higher scores in direct and relational aggressiveness, and physical and verbal victimization. In addition, playing action and role video games, which are related to violent contents, was associated with higher levels of direct aggression and relational victimization. Furthermore, positive correlations were found between problematic use of video games and all types of aggression and victimization. In conclusion, it is shown that the use of display devices is greatly related to levels of aggressiveness and victimization in school, revealing the importance of using properly these devices and promoting prosocial behaviours from different statements in order to alleviate this problem.
Keywords: aggressiveness; victimization; video games; school